Analysis of Actions Against The Law Case of Appointment of The Pagu Tribe Custom Leader (Sangaji) In North Halmahera Regency - Alimudin Boly; Husen Alting; Suwarti Suwarti (Syntax Corporation Indonesia, 2023)
This study aims to analyze the legitimacy of the appointment of the Pagu Tribe Chief based on the Customary Law of the Pagu people, as well as examine the considerations of the judges of the North Maluku High Court (PT) in deciding the case of appointing the Pagu Tribe Head of North Halmahera as an unlawful act (PMH). The research method used in this study is empirical legal research, namely research that looks at the application of laws and regulations in society. The results of this study indicate that validity of the Appointment of the Head of the Pagu Tribe based on the reason that the role of the Traditional Head in resolving land disputes in the Pagu Tribe is as a Peace Judge in customary trials and as a decision maker where the decision is binding for the parties to the dispute. Legal basis consideration of the judge of the District Court Number 13/Pdt.G/2020/PN.Tob decided the case of appointing the tribe head as the customary institutional administrator for the North Halmahera Pagu tribe was an unlawful act (PMH). Regarding loss of wealth (hermogenschade), compensation generally consists of compensation for losses suffered and also in the form of profits that one can expect to receive (gederfdewinst). In this regard, it is not as easy as predicted to determine the amount of compensation.